Paperless partogram as a bedside tool for the prevention of prolonged labour: A prospective observational study. - Dandapat, Atal Bihari; Rout, Rashmi Ranjan; Panda, Bikash Ranjan; Mohanty, Bhawani Shankar (Student's Journal of Health Research Africa, 2025)
Background Prolonged and obstructed labor, occurring in roughly 5% of deliveries, is a major cause of maternal and perinatal complications. Continuous monitoring of labor, timely recognition of deviations, and appropriate intervention are vital in reducing adverse outcomes. A more straightforward way to monitor the course of labor, the paperless partogram aids physicians in deciding the appropriate time for intervention and indicating when referral to higher centers with cesarean facilities is necessary. This study evaluated its effectiveness in preventing prolonged labor. Materials and Methods: A prospective study was carried out among 318 primigravida women with uncomplicated singleton pregnancies in cephalic presentation who presented in spontaneous active labor at the Department of Obstetrics and Gynecology, VSS Institute of Medical Science and Research, Burla. Alert ETD (anticipated time of delivery) and Action ETD parameters were used to track labor. Results: The mean age of participants was 24.6 ± 3.2 years. Most belonged to rural areas (68%) and the lower socioeconomic class (61%). Twenty-two percent of women crossed the Alert ETD, while only 1% exceeded the Action ETD. The mean duration of the active phase of labor was 4.9 hours. The incidence of prolonged labor was 8%, with 7 forceps and 20 cesarean deliveries. Conclusion: The paperless partogram was found to be a simple, reliable, and effective tool for managing labor. Its use minimized the occurrence of prolonged labor and contributed to a reduction in maternal and neonatal complications as well as cesarean section rates. Recommendation: It should be incorporated into routine obstetric care, especially in low-resource settings.